A sacrificial layer strategy for photolithography on highly hydrophobic surface and its application for electrowetting devices - Han Zhang (Nature Portfolio, 2017)
Abstract Patterning micro-structures on highly hydrophobic surface by photolithography is usually inevitable for fabricating devices based on electrowetting effects. The key challenges for such photolithography processes are how to coat photoresist uniformly and maintain the hydrophobicity of the highly hydrophobic surface, which are usually two contradict aspects. Moreover, the patterned microstructure must adhere to the highly hydrophobic surface excellently, which is critical for device application. However, a simple and robust fabrication process that fulfills all the above requirements was seldom reported. In this paper, we developed a sacrificial layer photolithography strategy on highly hydrophobic surface. Photoresist is easily coated uniformly all over the substrate by introducing a sacrificial layer between the photoresist and the highly hydrophobic surface. The hydrophobicity of the exposed hydrophobic surface was maintained and the adhesion of the microstructures to the substrate is excellent. An electrowetting display sample was demonstrated by this fabrication strategy, which showed dynamic image displaying with response time less than 40 ms. The strategy is applicable to both rigid and flexible substrate and manufacturing compatible. We believe our developed photolithography process is important for research and development of devices based on electrowetting effect.